Transition From Parenteral to Enteral Nutrition and Postnatal Growth in Very Preterm Infants During Their First 28 Days of Life - Wang, Na; Zhang, Jia; Wang, Bo; Yu, Zhangbin; Han, Shuping; Wang, Huaiyan; Chen, Rongrong; Gu, Li; Gao, Yan; Hou, Weiwei; Lu, Xingxing (Frontiers in Pediatrics, 2022)
Background: The transition nutrition (TN) phase from parenteral to enteral nutrition is inevitable in preterm infants. Our purpose was to analyze nutrition practices for very preterm infants during the TN phase and its association with neonatal growth. Methods: Data from 268 preterm infants < 32 weeks from six neonatal intensive care units were analyzed retrospectively. The TN phase, defined by enteral feedings of 30-120 ml/kg/d, was divided into two stages: the early stage (30-70 ml/kg/d) and the late stage (80-120 ml/kg/d). Postnatal growth failure (PGF) was defined as a 28-day growth velocity < 15 g/kg/d. Differences in amino acid and energy intake between the PGF and non-PGF groups were calculated, and the risk factors for PGF were identified using multivariate analysis. Results: The total protein intake from enteral and parenteral feedings decreased gradually during the TN phase, with a median of 3.16 g/kg/d. A significant difference was found in total protein intake [3.54 (3.15, 3.89) vs 3.33 (3.01, 3.68)] and parenteral amino acid intake [3.07 (2.60, 3.46) vs 2.85 (2.44, 3.20)] between the PGF and non-PGF groups in the early stage (P < 0.05). The higher the protein intake in the early stage of the TN phase and the older the infant's age (number of days) at the end of the TN phase, the lower the risk for PGF (P < 0.05). Conclusion: Increasing the total protein intake during the early stage of the TN phase, especially the parenteral amino acid intake can reduce the risk of PGF.